Rehabilitation of Patellofemoral Pain Syndrome - Duygu Çubukçu; Ayşe Sarsan (Archives of Rheumatology, 2008)
The term ‘patellofemoral pain syndrome (PFPS)’ is used for the clinical presentation with anterior knee pain related to changes in the patellofemoral articulation. Most of the patients with PFPS can be successfully treated once contributing factors are identified concerning the disease history and physical examination. Patellar malalignment is the most common cause. Factors which cause patellar malalignment include an increase in the Q angle, patella alta, an excessive pronation of subtalar joint, vastus medialis insufficiency and muscle tightness. Vastus medialis obliqius education, stretching exercises, the use of patellar taping, correction of abnormal pronation in subtalar joint and education of patients are the basic methods of rehabilitation of PFPS. (Rheumatism 2008; 23: 18-23)